2008
DOI: 10.1128/iai.00370-08
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic AMP Receptor Protein, CRP, Is Required for Both Virulence and Expression of the Minimal CRP Regulon in Yersinia pestis Biovar microtus

Abstract: The cyclic AMP receptor protein (CRP) is a bacterial regulator that controls more than 100 promoters, including those involved in catabolite repression. In the present study, a null deletion of the crp gene was constructed for Yersinia pestis bv. microtus strain 201. Microarray expression analysis disclosed that at least 6% of Y. pestis genes were affected by this mutation. Further reverse transcription-PCR and electrophoretic mobility shift assay analyses disclosed a set of 37 genes or putative operons to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
144
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(152 citation statements)
references
References 35 publications
6
144
0
2
Order By: Relevance
“…With this goal in mind, we constructed and evaluated an araC P BAD crp strain and, for comparison, an isogenic ⌬crp strain. Our results indicate that crp affects virulence in Y. pestis, consistent with what was found in a recent study in which a Y. pestis ⌬crp strain was shown to be highly attenuated when administered subcutaneously to mice (54). In that study, the authors found that the s.c. LD 50 in mice was approximately 1 ϫ 10 4 -fold higher than that of wild-type Y. pestis strain 201 (54).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…With this goal in mind, we constructed and evaluated an araC P BAD crp strain and, for comparison, an isogenic ⌬crp strain. Our results indicate that crp affects virulence in Y. pestis, consistent with what was found in a recent study in which a Y. pestis ⌬crp strain was shown to be highly attenuated when administered subcutaneously to mice (54). In that study, the authors found that the s.c. LD 50 in mice was approximately 1 ϫ 10 4 -fold higher than that of wild-type Y. pestis strain 201 (54).…”
Section: Discussionsupporting
confidence: 92%
“…Crp modulates expression of genes in many pathogenic bacteria, including Salmonella, Vibrio cholerae, Yersinia enterocolitica, and Y. pestis (10,38,44,54). Crp regulation occurs either directly, by binding to specific DNA sequences near the regulated gene, or indirectly, through the action of CyaR, a regulatory RNA (13).…”
mentioning
confidence: 99%
See 3 more Smart Citations